Direct-Pathway Spiny Projection Neuron Inhibition Evokes Transient Circuit Imbalance Manifested as Rotational Behavior. (15th January 2021) - Christensen, Maria; Nørr, Søren Emil; Gether, Ulrik; Rickhag, Mattias
Highlights: Ipsilateral rotations occurred in single turns or bursts in tetanus toxin light chain (TeLC)-expressing mice. Bursts of ipsilateral rotations in TeLC-expressing mice occurred in particular upon pharmacological modulation. Permanent, unilateral inhibition of dSPN activity is associated with a temporal circuit imbalance. Abstract: The striatum collects and integrates information from many different areas of the brain and propels this forward to the basal ganglia (BG) output structures. In this way, the striatum is playing a pivotal role in control of voluntary movements and is implicated in debilitating movement disorders such as Parkinson's disease. The functional backbone of the striatum is represented by direct pathway (dSPN) Drd1-expressing and indirect pathway (iSPN) Drd2-expressing spiny projection neurons (SPN), exerting opposite effects on movement. In rodent models of striatal function, unilateral dopamine deprivation is known to induce ipsilateral rotational behavior. To further study imbalance of the BG circuit and striatal domain influence on behavioral outcome, we employed a viral approach based on tetanus toxin light chain (TeLC) activity for permanent inhibition of dSPN activity in dorsomedial striatum (DMS). Cre-dependent TeLC injected unilaterally into the DMS of Drd1-Cre mice resulted in robust expression of TeLC in the dSPN cell populations as shown by immunohistochemistry. In the TeLC expressing mice, but not in control mice, we observed ipsilateral rotations that were enhanced upon administration of amphetamine to augment striatal dopamine levels. We argue that the observed single turns of ipsilateral rotations occur because of TeLC-mediated silencing of dSPN activity in one hemisphere, causing unresponsiveness to dopamine transients during movement initiation. This evokes a temporal BG circuit imbalance manifested as short bursts of rotations, particular evident during extrinsic dopaminergic modulation.